Innovation adoption in a hospital. The role of perceived innovation attributes in the adoption intention - Worum, Haakon (UiT Norges arktiske universitet, 2014)
Research on innovation attributes- and adoption is an inconclusive branch that has been deemed highly dependent on its context. Attempts to create general scales of measuring innovation attributes as an antecedent of adoption have all failed as evident by the amassed critique of such scales. The only concurrence within this research discipline is that scales that intend to explain innovation adoption as a consequence of perceptions of certain innovation attributes, needs to be adjusted to their context. The purpose of this study is not to develop a general scale of such attributes, nor is it to test existing scales. Instead, this study focuses on how the relationship between perceptions of innovation attributes and innovation adoption unfolds in a specific context. The context in this study is the hospital sector, where one department within the University Hospital of Northern Norway is currently facing a decision of whether or not to adopt an innovation that might potentially the work procedures within department. I felt that the hospital sector was particularly interesting in terms of explaining how innovation adoption occurs. The reason for this this is that hospitals are highly research-intensive institutions with a high demand for innovative solutions. Prior to this study, it was assumed that the course of the adoption-decision process was unique in hospitals due to organizational and professional complexities. An existing framework that can be used to explain the relationship between innovation attributes and innovation adoption was applied, and modified in order to adjust to the assumed complexities of the hospital sector. The result was a context-adjusted model that attempted to explain how perceptions of innovation attributes affected the intention of adopting the innovation. The findings in this study confirmed that this particular case within the hospital sector was distinct in terms of how perceptions of innovation attributes affected the adoption intention. This distinction turned out to be a result ...